2021
DOI: 10.1016/j.jbusvent.2020.106015
|View full text |Cite
|
Sign up to set email alerts
|

How does entrepreneurial failure change an entrepreneur's digital identity? Evidence from Twitter data

Abstract: We assess whether and how entrepreneurs' digital identities change in response to entrepreneurial failure based on a sample of 760 entrepreneurs who experienced failure. We analyze a longitudinal dataset of Twitter messages before, during, and after a business failure with a language-based method of computerized text analysis. The results of our explorative research indicate that the financial, social, and psychological consequences of failure are reflected in entrepreneurs' Tweets and lead to changes in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 61 publications
1
58
0
Order By: Relevance
“…This study is based on a large set of submissions and comments from an online community of entrepreneurs during the COVID-19 pandemic. In line with other studies that investigate big datasets in the entrepreneurship literature (e.g., Bloh et al, 2020 ; Fisch & Block, 2021 ; Obschonka & Fisch, 2018 ; Obschonka et al, 2017 , 2020 ; Prüfer & Prüfer, 2020 ), we used a stepwise process to access information within the vast amount of posts, which helps us answer our research question. More precisely, we investigate community conversations in four steps (Table 1 ) .…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…This study is based on a large set of submissions and comments from an online community of entrepreneurs during the COVID-19 pandemic. In line with other studies that investigate big datasets in the entrepreneurship literature (e.g., Bloh et al, 2020 ; Fisch & Block, 2021 ; Obschonka & Fisch, 2018 ; Obschonka et al, 2017 , 2020 ; Prüfer & Prüfer, 2020 ), we used a stepwise process to access information within the vast amount of posts, which helps us answer our research question. More precisely, we investigate community conversations in four steps (Table 1 ) .…”
Section: Methodsmentioning
confidence: 97%
“…For example, the community will react differently depending on whether entrepreneurs desire to use the community to test out a new opportunity (Autio et al, 2013 ), or whether they are seeking to deal with failure (c.f. Fisch & Block, 2021 ). This phenomenon where a community may shift its characteristics and offer different responses depending on the inquiry is known to information systems research as affordances (Leonardi, 2011 ; Leonardi & Treem, 2012 ), a theoretical perspective that enables us to understand online interactions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship studies have long shown that innovative data sets such as Twitter data may enable researchers to circumvent low response rates and method biases (e.g., Fisch and Block 2020). In fact, a very current study (not included in the review) does show that Twitter data in sport contexts can be obtained to measures narcissism (Grijalva et al 2019).…”
Section: Inclusion Of Innovative Datamentioning
confidence: 82%
“…These findings further support the argument that entrepreneurship is associated with more positive emotional expressions on social media platforms, and demonstrate that, controlling for the characteristics of the entrepreneur, entrepreneurial actions are associated with increased positivity. Finally, our study contributes to recent research that has examined the digital footprints of entrepreneurs using computerized text analyses [47][48][49].…”
Section: Introductionmentioning
confidence: 81%